2018
DOI: 10.15666/aeer/1604_40814095
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Trace Metals in Mangrove Plant Soneratia Caseoralis in Songkhla Lake, Thailand

Abstract: Mangrove sediment and mangrove plant Soneratia caseolaris in Songkhla Lake, Thailand have been increasingly threatened by trace metal pollution. Mangroves receive trace metal pollution from upstream areas and the sea. However, little is known about the mangrove plant's capacity to uptake and store trace metals. In this study, the concentrations of As, Cd, Pb and Zn in mangrove plant parts (leaf, root, and bark) of Sonneratia caseolaris and sediments were determined. Sediment and plant samples were digested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These rivers collect urban waste as well as industrial and agricultural waste. The potential sources of heavy metal in the sediment of Songkhla Lagoon (the outer section) include municipal waste from the large and rapidly expanding cities of Songkhla province, as well as agricultural and industrial discharges transported via the U-Taphao canal (Sompongchaiyakul and Sirinawin, 2007;Pradit et al, 2018). As and Cu are employed in the parawood business as wood preservatives near to the lagoon Potential ecological risk indices (R¡) of lagoon sediment.…”
Section: Potential Sources Of Microplastics and Heavy Metalsmentioning
confidence: 99%
“…These rivers collect urban waste as well as industrial and agricultural waste. The potential sources of heavy metal in the sediment of Songkhla Lagoon (the outer section) include municipal waste from the large and rapidly expanding cities of Songkhla province, as well as agricultural and industrial discharges transported via the U-Taphao canal (Sompongchaiyakul and Sirinawin, 2007;Pradit et al, 2018). As and Cu are employed in the parawood business as wood preservatives near to the lagoon Potential ecological risk indices (R¡) of lagoon sediment.…”
Section: Potential Sources Of Microplastics and Heavy Metalsmentioning
confidence: 99%
“…These studies have shown that canals and their vicinities were associated with abundant trace elements because of municipal, agricultural, and industrial discharges entering the lake through the canals. Furthermore, a recent study, which analyzing the concentrations of As, Cd, Pb, and Zn in mangrove plants (leaves, roots, and bark) and sediments, revealed heavy pollution of As (Pradit et al, 2018). However, research on sedimentary trace metal history, which can help improve understanding of the influence of human activities, remains scarce.…”
Section: Introductionmentioning
confidence: 99%